2010
DOI: 10.1111/j.1365-3156.2010.02561.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth response to antiretroviral treatment in HIV-infected children: a cohort study from Lilongwe, Malawi

Abstract: Summary Objective Malnutrition is common in HIV-infected children in Africa and an indication for antiretroviral treatment (ART). We examined anthropometric status and response to ART in children treated at a large public-sector clinic in Malawi. Methods All children aged <15 years who started ART between January 2001 and December 2006 were included and followed until March 2008. Weight and height were measured at regular intervals from 1 year before to 2 years after the start of ART. Sex- and age-standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 32 publications
5
62
1
2
Order By: Relevance
“…To model the nonlinear increase of the anthropometric measurements on ART over time most accurately, we used a second order fractional polynomial transformation of time 22 as described previously. 1 All available weight and height measurements from ART initiation up to 3 years afterward were included in the analysis, provided the child had a baseline and at least 1 weight or height measurement after the start of ART. (1997-2005, 2005-2006, 2006-2007, and 2008-2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To model the nonlinear increase of the anthropometric measurements on ART over time most accurately, we used a second order fractional polynomial transformation of time 22 as described previously. 1 All available weight and height measurements from ART initiation up to 3 years afterward were included in the analysis, provided the child had a baseline and at least 1 weight or height measurement after the start of ART. (1997-2005, 2005-2006, 2006-2007, and 2008-2010).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Reasons for growth retardation are multifactorial and include genetic and environmental factors such as poor nutrition, low socioeconomic status, and infection by different pathogens. 4,5 All of these factors are interrelated and may decrease immunity and lead to malabsorption of food and to endocrine dysfunction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, among the Malawian children neither the median weightfor-age Z-score nor the height-for-age Z-score reached normal values after two years on HAART among children who were underweight or stunted at initiation of HAART [22]. Likewise a study from Tanzania revealed that HIV-infected children on HAART were more likely to be underweight and/or wasted compared to HIV-uninfected children [24].…”
Section: Nutritional Status Of Hiv-infected Childrenmentioning
confidence: 99%
“…HIV-infected children from Malawi and Uganda had significant improvements in weight-for-age and height-forage Z-scores within one to two years of HAART initiation [22,23].…”
Section: Nutritional Status Of Hiv-infected Childrenmentioning
confidence: 99%